Numerical study on fatigue life of spot welded for automotive components - Noor, M. M.; Rahman, M. M.; Sani, M. S.M.; Julie Juliewatty, Mohammed; Nik Mohamed, Nik Mohd Zuki; Rose, Ahmad Nasser Mohd (2008)
The automotive industries are always carrying out the optimizations on vehicle's performance and cost. One of the ways is by using different materials at different vehicle locations to utilize the materials' functionalities to the fullest extent. Engineers are becoming more and more open minded about choosing the best material for certain applications. Today aluminium and steel are the most important construction materials for the mass production of automotive structures. The combined use of these materials offers automotive designers the best compromise between weight reduction and strength of the body. With the trend to multiple materials in vehicle designs, a reliable joining method must be developed and evaluated. Continuing pressure to improve quality, minimize cost and meet fuel economy, high environmental stand and safety requirements, has led a demand for automotive industries to use lighter and stronger materials. High strength steels are used resulting in significant weight reductions in high volume vehicles. However, the use of new materials raises challenges for the manufacturing processes. Spot welding is the predominant joining techniques in the assembly process. Assessing the spot welding quality is a very important issue in ensuring vehicle structure integrity. A scientific and systematic study of quality of resistance spot welding will benefit the automotive industry by producing high quality and low cost automobiles through consistent and quality welding.